Representation of visual uncertainty through neural gain variability - Olivier J. Hénaff (Nature Portfolio, 2020)
How does the brain represent sensory uncertainty? The authors find that neural gain variability tracks stimulus uncertainty across the visual hierarchy and explain their findings with a simple generalization of canonical models of neural computation.